Serum lactate level is an independent predictor of mortality in cardiac stab wounds – A South African experience - Victor Kong; Jonathan Ko; Anantha Narayan; Summer Hassan; Priscilla Leow; Jia Lim; John Bruce; Grant Laing; Damian Clarke (Surgery in Practice and Science, 2023)
Introduction: Despite dramatic advances in the care of trauma patients over the last fifty years, cardiac stab wounds (CSW) remain highly lethal, and the specific relationship between serum lactate level and mortality is unknown. Methods: A retrospective review was conducted on all patients who presented with intraoperatively confirmed CSW from January 2008 to January 2020 at a major trauma centre in South Africa. Admission serum lactate level and patients' clinical outcomes were reviewed. Results: During the 12-year study period, a total of 236 patients were included (84% male, mean age: 28 years). Mean value of admission physiology: Systolic Blood Pressure: 79 mmHg, pH: 7.2, Serum Lactate: 6 mmol/l. Surgical access was via: median sternotomy in 65% (153/236) and the remaining 35% (83/236) via lateral thoracotomy. In 92% (217/236), there was a single cardiac chamber injury; in the remaining 8% (19/236), multiple cardiac chambers were injured. The overall mortality was 18% (43/236). Lactate was a significant predictor of mortality (AUC 93.8, p<0.001). Using a cut-off point of ≥ 7.4 mmol/l, the sensitivity was 93%, and the specificity was 91% in predicting mortality. A lactate ≥ 7.4 mmol/l was associated with 242 times higher odds of mortality (95% CI 38 – 1551). Conclusion: CSWs remain highly lethal, and an initial serum lactate level ≥ 7.4 mmol/l is associated with increased mortality.